2021
DOI: 10.1016/j.jacl.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of severe hypertriglyceridemia and pancreatitis in familial partial lipodystrophy type 2

Abstract: Familial partial lipodystrophy (FPLD) is a rare Mendelian condition listed in the differential diagnosis of severe hypertriglyceridemia (HTG) and pancreatitis. Here we determined the prevalence of severe HTG and pancreatitis among a cohort of 74 FPLD patients assessed in a lipid clinic. We studied lipid profiles from individuals with either of the two most common pathogenic monoallelic variants in LMNA , namely p.R482Q (N = 51) and p.R482W (N = 23). In total, 28 (37.8%) patients with a mean age of 41.8 ± 14.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Most authors propose that the severity of lipid disturbances translates directly into body fat reduction, which is more pronounced in women. Moreover, Lazarte et al suggest that the risk of severe hypertriglyceridemia and consequent pancreatitis in FPLD2 depends on the co-occurrence of diabetes [32]. Our index patient and her mother also demonstrate severe hypertriglyceridemia with features of high cellular insulin resistance, which supports the findings of other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Most authors propose that the severity of lipid disturbances translates directly into body fat reduction, which is more pronounced in women. Moreover, Lazarte et al suggest that the risk of severe hypertriglyceridemia and consequent pancreatitis in FPLD2 depends on the co-occurrence of diabetes [32]. Our index patient and her mother also demonstrate severe hypertriglyceridemia with features of high cellular insulin resistance, which supports the findings of other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Severe HTG has also been observed in individuals with familial partial lipodystrophy (FLPD) subtype 2 caused by pathogenic rare variants in LMNA (OMIM 150330) encoding nuclear lamin A/C [ 69 ]. In these patients, hypertriglyceridemia severity is typically mild-to-moderate.…”
Section: Genetic Predisposition To Severe Hypertriglyceridemia and Pa...mentioning
confidence: 99%
“…In these patients, hypertriglyceridemia severity is typically mild-to-moderate. However, about 15% of patients experience sustained severe hypertriglyceridemia >10 mmol/l and this subgroup has a very high lifetime risk of acute pancreatitis, emphasizing again that irrespective of the genetic background, the proximal determinant of pancreatitis risk is the severity of the triglyceride elevation [ 69 ].…”
Section: Genetic Predisposition To Severe Hypertriglyceridemia and Pa...mentioning
confidence: 99%
“…An observational study by Lazarte et al [16 & ] in FPLD patients found that the risk of severe HTG and pancreatitis depends on the presence of diabetes mellitus. Study participants with diabetes had, on average, moderate HTG, with 14.3% having severe HTG and 10.7% a history of pancreatitis [16 ]. It is recommended that triglycerides be measured at least annually, and a fasting lipid panel at diagnosis and annually after 10 years of age in patients with lipodystrophies [4].…”
Section: Dyslipidemiamentioning
confidence: 99%